(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The tannery industry in Bangladesh, particularly at the Savar Bangladesh Small & Cottage Industries Corporation (BSCIC) Tannery Estate, presents significant occupational health risks due to hazardous chemicals and outdated processes. Despite relocation from Hazaribagh and efforts to improve occupational health and safety (OHS) standards, compliance remains insufficient, leading to chronic health issues such as respiratory disorders, skin conditions, and increased risk of cancer. This study investigates these health risks, particularly exposure to heavy metals like chromium, as well as biological agents, dust, and high noise levels from machinery. Using a cross-sectional design, data were collected through participatory observation, interviews and questionnaire survey from 205 tannery workers. Descriptive statistics and regression analysis reveal a high prevalence of skin diseases (48.78%) and respiratory problems (44.39%), exacerbated by poor ventilation (66.7%), minimal personal protective equipment (PPE) usage (46.3%), and inadequate healthcare access. Although 85.9% of workers are aware of chemical hazards, only 39.5% received formal training, highlighting gaps in safety education. The regression analysis showed a positive relationship between the number of years worked and the years of health problems, with the equation y=0.31x+1.38, indicating that for every additional year worked, health issues increase by 0.31 years. The R2 value of 0.44 suggests that 44% of the variation in health problems is explained by work duration, with other factors likely contributing. The findings underscore the urgent need for stricter enforcement of national regulations, such as the Bangladesh Labour Act 2006, and international frameworks, including ILO conventions, to improve workplace conditions. Improved environmental management, enhanced safety training, and better healthcare provisions are essential to protect workers’ health. The study also stresses aligning tannery practices with the Sustainable Development Goals (SDGs) related to good health, decent work, and responsible production, calling for immediate action from authorities to safeguard worker well-being. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 115-129, 2024